Efficient Master /Slave Computing Using Threshold Value Specification (International Journal of Engineering and Computer Science, 2013)
Recent day’s totaling famous study of master slave computing. Master slave computing to provide potential benefits are higher availability (multiple nodes to read from) and quicker response times (when doing reads from slaves). The proposed study of master slave computing work tells a study about Parallel Discrete Event Simulation (PDES) approach, it’s used to can easily be added or removed during execution. In the traditional system, the Master slave approach compares two overheads namely, Transmission and blocking time. In the master slave system, the master can order the modules to the worker (slave), the slave executes the modules by their order of slave. The successful sourcing computation values are computed based on the threshold value, where the threshold value, key, found value, computation. In the found value is equal to the threshold value where the algorithm is runs for the first request. After finishing the response can be executed. Finally this paper shows overall performance results with the comparison of found value and the threshold value specifications to confirm the security of information in the system.